Implementasi Aplikasi SIDASTER dalam Program Percepatan Penurunan Stunting di Kabupaten Madiun - Rosy Analistin, Angelia; Milwan, Milwan; Listiani, Teni (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study aims to provide an overview of the implementation of the SIDASTER application in the stunting reduction program in Madiun Regency. This research employs a qualitative method with a case study design to gain an in-depth understanding of the application's role in accelerating stunting reduction. The analysis is grounded in Van Meter and Van Horn's (1975) policy implementation theory, which emphasizes that effectiveness is determined by resource availability, communication quality, socio-political conditions, and implementer attitudes. However, the implementation of SIDASTER also demonstrates new dynamics not fully accommodated by this theoretical framework. The findings reveal both supporting and inhibiting factors in the implementation process. Supporting factors include adequate human resources, technological devices, internet connectivity, cross-sectoral coordination through formal and informal channels, local government policy and budget support, as well as positive attitudes among implementers. Conversely, inhibiting factors include limited digital literacy among village cadres, uneven internet infrastructure, high workloads, and the absence of a dedicated budget for digital system development. These constraints have resulted in slow and uneven data entry processes and hindered real-time data synchronization. The study highlights the need to strengthen human resource capacity, improve digital infrastructure, enhance cross-sectoral coordination, and allocate sufficient technological funding to ensure more effective and sustainable implementation of SIDASTER. This research contributes to a broader understanding of factors influencing the success of digital-based policy implementation at the local government level.